2017
DOI: 10.1111/1462-2920.13814
|View full text |Cite
|
Sign up to set email alerts
|

Type 4 pili are dispensable for biofilm development in the cyanobacterium Synechococcus elongatus

Abstract: The hair-like cell appendages denoted as type IV pili are crucial for biofilm formation in diverse eubacteria. The protein complex responsible for type IV pilus assembly is homologous with the type II protein secretion complex. In the cyanobacterium Synechococcus elongatus PCC 7942, the gene Synpcc7942_2071 encodes an ATPase homologue of type II/type IV systems. Here, we report that inactivation of Synpcc7942_2071 strongly affected the suite of proteins present in the extracellular milieu (exo-proteome) and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
72
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 66 publications
6
72
3
Order By: Relevance
“…microcins, often precedes their secretion (Michiels et al, ; Bobeica et al, ) and, therefore, we examined whether the putative microcin‐processing peptidase encoded by Synpcc7942_1127 affects extracellular levels of these proteins. Exoproteome analysis revealed higher levels of each of the EbfG proteins in extracellular culture fluids of T2SEΩ compared with WT (Nagar et al, ). In contrast, inactivation of Synpcc7942_1127 in combination with T2SEΩ significantly reduced the extracellular levels of EbfG proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…microcins, often precedes their secretion (Michiels et al, ; Bobeica et al, ) and, therefore, we examined whether the putative microcin‐processing peptidase encoded by Synpcc7942_1127 affects extracellular levels of these proteins. Exoproteome analysis revealed higher levels of each of the EbfG proteins in extracellular culture fluids of T2SEΩ compared with WT (Nagar et al, ). In contrast, inactivation of Synpcc7942_1127 in combination with T2SEΩ significantly reduced the extracellular levels of EbfG proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…, our data preclude PilC-mediated secretion of released factors 295 analogous to biofilm enhancers and inhibitors secreted by S. elongatus[62][63][64].…”
mentioning
confidence: 77%
“…This mutation is proposed to block an unidentified 118molecule that inhibits secretion of biofilm enhancing proteins in WT S. elongatus [63]. 119 A subsequent study found certain piliated S. elongatus mutants also underwent a degree 120 of sedimentation, adhesion, and biofilm formation compared to WT, indicating that loss 121 of Type IV pili is not a prerequisite for biofilm formation in S. elongatus [64].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The time course experiment has allowed us to assign the production of these proteins to nutrient-rich conditions with a peak of SynWH7803_1795 detection at day 7 (25.7%) and an average detection of 8.1% over the 100 days, whereas the detection was low (< 0.1%) in natural SW conditions. The remarkable ecological and physiological roles of the pili need further characterization although a recent study in Synechococcus elongatus suggests this structure may be involved in cell buoyancy (Nagar et al, 2017). Interestingly, both alkaline phosphatases were detected in the exoproteome of Synechococcus sp.…”
Section: Correlation Between Culture Growth and Exoproteomesmentioning
confidence: 99%